2019
DOI: 10.3390/molecules24061033
|View full text |Cite
|
Sign up to set email alerts
|

Application of Antimicrobial Nanoparticles in Dentistry

Abstract: Oral cavity incessantly encounters a plethora of microorganisms. Plaque biofilm—a major cause of caries, periodontitis and other dental diseases—is a complex community of bacteria or fungi that causes infection by protecting pathogenic microorganisms from external drug agents and escaping the host defense mechanisms. Antimicrobial nanoparticles are promising because of several advantages such as ultra-small sizes, large surface-area-to-mass ratio and special physical and chemical properties. To better summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
154
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 170 publications
(263 reference statements)
0
154
0
10
Order By: Relevance
“…Further studies are required to clarify the correlation of concentration and antimicrobial activity. Studies of the antimicrobial activity were performed following procedures reported to investigate intrinsically antimicrobial polymers based on poly((tertbutyl-amino)-methyl-styrene) [62][63][64][65][66] and coatings based on HPMC/lignin/chitosan [52]. Two different nutritions were used: sodium chloride (NaCl) and physiological saline solution (NB) of different concentrations (Figure 2).…”
Section: Antibacterial Activity Of Kraft Ligninmentioning
confidence: 99%
“…Further studies are required to clarify the correlation of concentration and antimicrobial activity. Studies of the antimicrobial activity were performed following procedures reported to investigate intrinsically antimicrobial polymers based on poly((tertbutyl-amino)-methyl-styrene) [62][63][64][65][66] and coatings based on HPMC/lignin/chitosan [52]. Two different nutritions were used: sodium chloride (NaCl) and physiological saline solution (NB) of different concentrations (Figure 2).…”
Section: Antibacterial Activity Of Kraft Ligninmentioning
confidence: 99%
“…Several hybrid materials can exhibit antimicrobial activity [1][2][3]. For example, in restorative dentistry, inorganic antibacterial nanoparticles (NPs) incorporated to resin composites effectively reduce microorganism biofilm formation [4]. Examples of inorganic NPs with intrinsic antimicrobial activity are those made of ZnO, MgO, CuO, metallic silver, or gold, metal hydroxides such as Mg(OH) 2 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Both silver nanoparticles [62][63][64] and biomimetic iron oxide nanoparticles have been shown to impair biofilm formation and to prevent dentinal tubule infection by E. faecalis [65]. This approach should work even in teeth with complex canals [66].…”
Section: Antimicrobial Medicamentsmentioning
confidence: 99%